Incidence of sudden cardiac death in the young: a systematic review - Joyce Yeung; Kurtis Poole; Sian Taylor-Phillips; Aileen Clarke; Gavin D Perkins; Keith Couper; William Bradlow; Oliver Putt; Richard Field; Pamela Royle (BMJ Open)
Objective To summarise studies describing incidence of sudden cardiac death in a general population of young individuals to inform screening policy.Design Systematic review.Data sources Database searches of MEDLINE, EMBASE and the Cochrane library (all inception to current) on 29 April 2019 (updated 16 November 2019), and forward/backward citation tracking of eligible studies.Study eligibility criteria All studies that reported incidence of sudden cardiac death in young individuals (12–39 years) in a general population, with no restriction on language or date. Planned subgroups were incidence by age, sex, race and athletic status (including military personnel).Data extraction Two reviewers independently assessed study eligibility, extracted study data and assessed risk of bias using the Joanna Briggs Institute critical appraisal checklist for prevalence studies.Analysis Reported incidence of sudden cardiac death in the young per 100 000 person-years.Results 38 studies that reported incidence across five continents. We identified substantial heterogeneity in population, sudden cardiac death definition, and case ascertainment methods, precluding meta-analysis. Median reported follow-up years was 6.97 million (IQR 2.34 million–23.70 million) and number of sudden cardiac death cases was 64 (IQR 40–251). In the general population, the median of reported incidence was 1.7 sudden cardiac death per 100 000 person-years (IQR 1.3–2.6, range 0.75–11.9). Most studies (n=14, 54%) reported an incidence between one and two cases per 100 000 person-years. Incidence was higher in males and older individuals.Conclusions This systematic review identified variability in the reported incidence of sudden cardiac death in the young across studies. Most studies reported an incidence between one and two cases per 100 000 person-years.PROSPERO registration number CRD42019120563.